MEMBANGUN KESEJAHTERAAN DAN KESEHATAN KEUANGAN MELALUI PENDEKATAN AKUNTANSI SYARIAH DI DINAS KESEHATAN KOTA MEDAN - Husna, Rifdah Nur; Kamilah, K (Relawan Jurnal Indonesia, 2024)
Healthy and sustainable financial management is the main focus in efforts to improve community welfare, especially in the health sector. One approach that can be used is sharia accounting, which prioritizes the principles of justice, transparency and sustainability in financial management. This study aims to analyze how the implementation of sharia accounting in the Medan City Health Service can help build financial prosperity and health. The research method used is a case study by collecting data through interviews, observation and document analysis. The research results show that the implementation of sharia accounting in the Medan City Health Service has made a positive contribution in building community welfare through more transparent, efficient and sustainable financial management. However, further efforts are still needed to optimize the benefits of implementing sharia accounting in improving overall financial welfare and health.